A review of crack propagation modeling using peridynamics - Dias, João Paulo; Bazani, Márcio Antonio [UNESP]; Paschoalini, Amarildo Tabone [UNESP]; Barbanti, Luciano [UNESP] (Springer Nature, 2017)
Improvements on prognostics and health management (PHM) techniques are extremely important in order to prevent system failure and reduce costs with maintenance and machine downtime. In the particular case of system components subjected to fracture failure, such improvements are closely related to the effect of crack propagation mechanisms on the quantification of the system remaining useful life (RUL). This chapter presents a review of the state-of-the-art of crack propagation modeling techniques and discusses the current limitations of finite elements methods (FEM) to model structures with cracks. The chapter also gives special attention to peridynamics (PD), a continuum non-local approach that has been considered to be a promising method to model structures with crack discontinuities. Therefore, the purpose of this chapter is to answer the following research question: Can PD be a potential alternative to FEM on modeling of crack propagation problems in predicting RUL? In order to answer this question, a literature review of the most relevant works on crack modeling field is presented and discussed. An application that involves a classical 2D crack propagation problem in a pre-notched glass plate is also included, in which comparisons between numerical predictions and experimental observations were performed. It was shown that PD produces more accurate predictions than FEM based-methods from both qualitative and quantitative perspectives.
Keywords: Crack propagation modeling; Peridynamics; Prognostics and health management